Pengaruh January Effect, Convertible Bond, Tingkat Suku Bunga Dan Volume Perdagangan Saham Terhadap Harga Saham Pada Perusahaan Yang Terdaftar Di Indeks LQ 45 Periode 2011 – 2015 - Ichdan, Dany Amrul; Lukman, Iing; Shinta, Dayu Renanda (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2021)
Stock prices are fluctuating in every company that tends to differ, this is the reason why the researcher is interested in taking the dependent variable in this research that is stock price. Because of its fluctuating nature is also the researchers want to investigate what are the factors that cause the stock price itself is fluctuating.This study aims to determine whether there is influence between January Effect, Convertible Bond, Interest Rate and Stock Trading Volume have an effect on Stock Price with Partial Test (Test t) and SimultanTest (Test F).The population of this study was taken from 45 LQ 45 Index of companies listing from 2011 to 2015 period, using Purposive Sampling method so that there are 22 companies consistently in LQ 45 Index. Data analysis method using IBM SPSS Statistiks 24 for Windows software and Microsoft Excel 2007 software.The result of this research is variable of January Effect, Interest Rate and Stock Trading Volume Has No Influence on Stock Price while Convertible Bond has significant negative influence to stock price. Based on the F test of January Effect variable, Convertible Bond, Interest Rate and Stock Trading Volume together affect the stock price.Keywords: January Effect, Convertible Bond, Interest Rate, Stock Trading Volume, Stock Price